EFEKTIVITAS PENGELOLAAN KEUANGAN DAERAH: PERAN MODERASI SISTEM PENGENDALIAN INTERN PEMERINTAH - Nana Santika; Taufeni Taufik; Devi Savitri (CURRENT: Jurnal Kajian Akuntansi dan Bisnis Terkini, 2021)
This study aims to determine the effect of employee performance, regional financial accounting systems, and human resource competencies on the effectiveness of regional financial management which is moderated by the government's internal control system. This research was conducted at Pelalawan District OPD. The data used in this study are primary data that is a questionnaire. The population in this study were employees who worked at the Regional Apparatus Organization in Pelalawan Regency. This study uses purposive sampling. Of 81respondent who participated indicate that: Employee performance and the regional financial accounting system influence the effectiveness of regional financial management but Human resource competence does not affect the effectiveness of regional financial management. The government's internal control system can moderate the effect of employee performance, the regional financial accounting system, and human resources on the effectiveness of regional financial management.